Serum modified HDL was associated with cardiovascular disease in a Japanese community-based cohort. (13th November 2019) - Okamura, T; Sata, M; Iida, M; Kakino, A; Harada, S; Hirata, A; Usami, Y; Sugiyama, D; Sawamura, T; Takabayashi, T
Abstract: Background: Previous studies have shown that high density lipoprotein (HDL) is protective against cardiovascular disease (CVD). However, recent studies suggested that function of HDL was more important than HDL cholesterol levels. The present study aimed to clarify the relationship between modified HDL levels and CVD incidence. Methods: LOX-1 (lectin-like oxidized LDL receptor) is the receptor that mediates modified LDL (low density lipoprotein) activity; however, some lipoproteins with apolipoprotein A1 (Apo A-1) are also bonded to LOX-1. In this study, serum LOX-1 ligand containing Apo A-1 was defined as modified HDL, which were measured by our new development method. We conducted a nested case-control study in a Japanese cohort study, involving 11, 002 community dwellers. During 4.0 years follow-up, we observed 127 new CVD onsets. For each CVD case, age and sex matched three controls were randomly selected (N = 381). Serum samples collected at baseline survey stored at − 80 °C were used for the measurement of modified HDL. We estimated multivariable-adjusted odds ratio (OR) and 95% confidence interval (CI) for the association between modified HDL levels and CVD by conditional logistic regression. Results: Modified HDL levels were associated with increased risk of CVD (OR for one unit increase of log transformed modified HDL, 2.05: 95% CI, 1.16-3.62) after adjustment for body mass index, hypertension, diabetes, LDL cholesterol, HDL cholesterol, lipid lowering agents, chronic kidney disease, smoking and alcohol drinking. The magnitude of OR was almost equivalent to those of hypertension and diabetes, which were 2.33 (95% CI, 1.37-3.98) and 2.61 (95% CI, 1.48-4.59), respectively. On the other hands, other lipids markers showed relatively weak associations with CVD. Conclusions: Serum modified HDL, i.e., LOX-1 ligand containing Apo A-1, might be a novel predictive marker for CVD in apparently healthy individuals. Key messages: Recent epidemiologic studies suggested that function of high-density lipoprotein (HDL) was more important than HDL cholesterol level itself to predict cardiovascular disease. Modified HDL measured by a novel cell-free, non-fluorescent method as LOX-1 ligand containing Apo A-1, was a predictive marker for CVD after adjusting for other traditional risk factors.